2005
DOI: 10.4049/jimmunol.174.6.3179
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse CD1d Cytoplasmic Tail Mediates CD1d Trafficking and Antigen Presentation by Adaptor Protein 3-Dependent and -Independent Mechanisms

Abstract: The short cytoplasmic tail of mouse CD1d (mCD1d) is required for its endosomal localization, for the presentation of some glycolipid Ags, and for the development of Vα14i NKT cells. This tail has a four-amino acid Tyr-containing motif, Tyr-Gln-Asp-Ile (YQDI), similar to those sequences known to be important for the interaction with adaptor protein complexes (AP) that mediate the endosomal localization of many different proteins. In fact, mCD1d has been shown previously to interact with the AP-3 adaptor complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 43 publications
1
51
0
1
Order By: Relevance
“…The human lymphoblastoid cell line 3023 (a derivative of LCL 721.174) was used to generate the transfectants (29). The tail-deleted CD1d molecules lack the final 10 aa residues of the cytoplasmic tail, which includes the AP-2 internalization motif and a lysine residue that is a target for ubiquitination (15,17,33). Hence, because they lack the known signals for internalization into the endosomal system, the tail-deleted CD1d molecules should undergo little or no endosomal recycling, whereas the wild-type should recycle normally.…”
Section: Nkt Cell Autoreactive Responses Are Independent Of Cd1d Endomentioning
confidence: 99%
See 1 more Smart Citation
“…The human lymphoblastoid cell line 3023 (a derivative of LCL 721.174) was used to generate the transfectants (29). The tail-deleted CD1d molecules lack the final 10 aa residues of the cytoplasmic tail, which includes the AP-2 internalization motif and a lysine residue that is a target for ubiquitination (15,17,33). Hence, because they lack the known signals for internalization into the endosomal system, the tail-deleted CD1d molecules should undergo little or no endosomal recycling, whereas the wild-type should recycle normally.…”
Section: Nkt Cell Autoreactive Responses Are Independent Of Cd1d Endomentioning
confidence: 99%
“…Four AP complexes (AP-1,-2,-3,-4) have been identified that bind to tyrosine or dileucine amino acid motifs in the cytoplasmic tails of transmembrane proteins (14). The cytoplasmic tail sequences of human and murine CD1d molecules both contain tyrosine-based motifs that mediate binding to the AP-2 complex, but the murine CD1d sequence also binds to the AP-3 complex, whereas the human CD1d sequence does not (15)(16)(17). The AP-2 complex mediates internalization from the cell surface into early endosomes, and the AP-3 complex directs trafficking from early endosomes to lysosomes (14).…”
mentioning
confidence: 99%
“…Deletion of the YxxI motif by the deletion of the CD1d cytoplasmic tail (CD1d-TD) resulted in a defect in type I NKT cell development and activation (11)(12)(13)16). The tyrosine-based motif in the cytoplasmic tail of mCD1d or human CD1b interacts with the m subunit of adaptor protein-3 (AP-3), which aids in the transport of CD1d to endosomal or lysosomal compartments (17)(18)(19)(20). A deficiency in AP-3 also inhibits the development of iNKT cells (18).…”
mentioning
confidence: 99%
“…Previous studies have shown that, at steady state, most of the CD1d molecules normally reside in the lysosomal compartment, from which they undergo prolonged recycling back and forth to the plasma membrane. This movement is governed by a tyrosine motif in the intracytoplasmic tail of CD1d that binds AP-2 and AP-3 (19)(20)(21). CD1d tail-truncated mutants fail to present many lipids, including the Vα14 NKT ligand iGb3, or the di-or triglycosylated derivatives of αGalCer that require processing by lysosomal glycosidases before recognition by Vα14 NKT cells.…”
Section: Discussionmentioning
confidence: 99%